The Influence of Digital Competence and Administrative Role on the Independence of Electronic Health Record Management in Hospitals - Biendha Ulfatullaily; Pipit Festi Wiliyanarti; Yudied Agung Mirasa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Background: The digital transformation of healthcare has positioned Electronic Health Records (EHR) as an essential component of patient care and health information management. The successful implementation of EHR systems depends largely on healthcare professionals' digital competence and the effectiveness of administrative roles. Objective: This study analyzes the influence of digital competence and administrative roles on the independence of electronic health record management in hospitals. Methods: A quantitative cross-sectional design was employed. Data were collected through structured questionnaires distributed to healthcare professionals, medical record personnel, and administrative staff at Muhammadiyah Hospital Gresik. Using purposive sampling, 66 respondents were selected based on Green's formula (1991). Multiple linear regression analysis with SPSS was conducted to examine the partial and simultaneous effects of the independent variables. Results: Digital competence significantly enhanced the independence of EHR management by improving users' ability to operate EHR systems autonomously. Administrative roles also showed a significant positive effect through effective documentation governance, compliance with standard operating procedures, and coordination across units. Together, both variables significantly influenced EHR management independence. Conclusion: Strengthening digital competence and administrative governance is essential to achieving sustainable and independent electronic health record management in hospitals.